‘If you have a problem with your heart, you have a problem with your life’: Self-perception and behaviour in relation to the risk of ischaemic heart disease in people living with HIV - Ronel Roos; Hellen Myezwa; Helena Van Aswegen (African Journal of Primary Health Care & Family Medicine, 2015)
Background: Ischaemic heart disease (IHD) is a global health problem and specifically relevant in the African context, as the presence of risk factors for IHD is increasing. People living with the human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) (PLWHA) are at increased risk for IHD due to increased longevity, treatment-specific causes and viral effects.